In‐vitro and in‐vivo evaluation of austocystin D liposomes. (16th November 2012) - Li, Shuo; Hu, Jie; Zhang, Linan; Zhang, Li; Sun, Yongjun; Xie, Yinghua; Wu, Shaomei; Liu, Lei; Gao, Zibin
Abstract: Objectives: The purpose this study is to enhance the anti‐tumour activity of austocystin D (AD) by AD‐loaded liposomes (AD‐Ls). Methods: AD‐Ls were prepared by the film dispersion–ultrasonication method and characterized in terms of particle size and zeta potential, encapsulation efficiency and in‐vitro drug release. In vivo, the pharmacokinetics, biodistribution and anti‐tumour effect were also compared with those of the solution. Key findings: The obtained liposomes were a mildly translucent suspension, with a particle size of 71.26 ± 6.43 nm, a polydispersity index of 0.259 ± 0.017 and a zeta potential of −9.9 ± 1.8 mV. Transmission electron microscope examination showed that the liposomes had a spherical shape and a multilayer structure. The encapsulation efficiency ofAD‐Ls was 83.74 ± 1.26%. AD was continuously released from liposomes up to 72 h in in‐vitro experiments. The growth of HT‐29 tumours in animal models was controlled more effectively by AD‐LS than by AD solution. Pharmacokinetic study showed that AD‐Ls had higher t½β and mean retention time. Biodistribution results in tumour‐bearing mice showed that the AD‐LS could target to liver and tumour. Conclusions: This study indicates that AD‐Ls are a potential carrier of AD for the treatment of tumours in the liver, increasing the cure efficiency and decreasing the side effects on other tissues.